2021
DOI: 10.1039/d1lc00218j
|View full text |Cite
|
Sign up to set email alerts
|

Advanced continuous-flow microfluidic device for parallel screening of crystal polymorphs, morphology, and kinetics at controlled supersaturation

Abstract: A flow-controlled microfluidic device for parallel and combinatorial screening of crystalline materials can profoundly impact the discovery and development of active pharmaceutical ingredients and other crystalline materials. While the existing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…A recent advancement in crystal growth rate measurements is the microfluidic device reported by Coliaie et al 44 Their setup allows for crystal growth to be observed under constant supersaturation after crystals are nucleated inside the set-up by the addition of an antisolvent. The cell features eight separate micromixers where crystals are nucleated and grown.…”
Section: A Short Overview On Crystal Growth Ratementioning
confidence: 99%
“…A recent advancement in crystal growth rate measurements is the microfluidic device reported by Coliaie et al 44 Their setup allows for crystal growth to be observed under constant supersaturation after crystals are nucleated inside the set-up by the addition of an antisolvent. The cell features eight separate micromixers where crystals are nucleated and grown.…”
Section: A Short Overview On Crystal Growth Ratementioning
confidence: 99%
“…The residence time of solutions in these tiny micromixers (up to 4 mm height and 4 mm diameter) varies from a few seconds to a few minutes. 13 As the hot solution enters the micromixer from the bottom and rises upward, it will continuously cool down without reaching a steady temperature and thus developing a large temperature variation inside the micromixer. It is nearly impossible to attain equilibrium temperatures in a fully jacketed micromixer with these residence times.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Recent developments of continuousflow crystallization in microfluidic devices have enabled effective screening of the crystal morphology, polymorph, size, and kinetic data under controlled conditions. 12,13 These microfluidic devices have cylindrical micromixers with tangential inlets of entering solution at the bottom, which creates a cyclonic (or rotational) flow to trap nucleated crystals. The cyclonic flow in the micromixer provides uniform mixing and isothermal conditions to achieve constant supersaturations while allowing the steady growth of trapped crystals.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an easy-to-adapt and affordable photosensitive turbidity sensor was developed and integrated into a novel continuous-flow microfluidic device for detecting the LLPS boundaries. [20][21][22][23][24] The continuous-flow microfluidic device provides uniform mixing by inducing cyclonic flow inside the micromixer. The turbidity sensor consists of a photodiode as the detector and an infrared light-emitting diode (LED) light that provides the light source.…”
Section: Introductionmentioning
confidence: 99%